(untitled) (Revista Peruana de Investigación Educativa, 2024)
Interactive communication between teacher and student is very important in virtual and blended environments, observed from the socio-emotional perspective, to achieve meaningful learning; The objective of the research was to determine the level of closeness of the teacher both in virtual and blended classes during the semesters 2021-II and 2022-I The results indicate that the level of perception of the students about empathy, interaction, and the use and management of the virtual platform by teachers in the two semesters was high, concluding that there is a significant difference between the level of closeness of the teacher of the 2021-II and 2022-I semester, concluding that it is important to build a relationship in the virtual environment between teacher-student, both quality and effective for this purpose, through the successful and assertive use of audiovisual content, as well How to check the use that students give to social networks, especially at this stage that there was confinement as a consequence of the COVID 19 pandemic.